Age and Paleobathymetry of Salodik Group in PohPagimana section, East Arm of Sulawesi Based on Foraminiferal Assemblages - Fakhruddin, Rakhmat; Kurniadi, Dedy (UIR PRESS, 2019)
Planktonic and benthic foraminiferal assemblages were used for age and paleobathymetry analysis of outcropping carbonate succession of the Salodik Group in Poh–Pagimana section, East Arm of Sulawesi. Twenty spot samples of carbonate rocks were collected from cut slope along the road between Poh and Pagimana. Age analysis conducted for each sample by its planktonic foraminifera assemblages and group into their age interval. The age range from Early Eocene to Pliocene. Benthic foraminiferal assemblages indicate paleobathymetry ranging from middle shelf to upper bathyal settings. Age analysis of the studied section show an older sediments (Early–Middle Eocene) overlie younger sediment (Early Miocene). This is interpreted as the evidence of thrust fault in the Poh–Pagimana section as part of thrust sheets of Batui thrust complex which imbricated on deformation zone. The youngest sediment which have suffered deformations shown by disordered age sequence is Pliocene in age (N20-21). The Eocene to Pliocene carbonate succession in the studied section was deposited relatively in the more basinward position compared to the carbonate-dominated sediments in the Tomori area which was deposited in the more landward position.